Semantic features of names of natural phenomena in Turkish and Kazakh proverbs and sayings - Suierkul Б.М.; Zharmukhanova Ж.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The reflection in proverbs and sayings of the names of natural phenomena in the Turkish and Kazakh languages is an urgent topic that requires a special study. The difference between the early and modern versions of the names of natural phenomena and their use in everyday life increases the importance of the topic of the article. In this regard, it seems appropriate to study the features of the use of paremia in oral speech in a comparative aspect. The semantic features of the names of natural phenomena, especially in a figurative sense, reflect the accumulated stock of knowledge in the centuries-old history of the people since the native speaker began to study and know himself in close relationship with the environment. The authors of the article aim to identify the linguistic mechanisms that indicate differences in their background knowledge by comparing and comparing proverbs and sayings of the Turkic peoples living in different regions with different climatic conditions. To achieve this goal, two tasks are set: to find and conduct a comparative analysis of the Kazakh equivalent of proverbs and sayings with the names of natural phenomena in the Turkish language, as well as to determine the final pragmatic intention of the speaker using the names of natural phenomena in direct and figurative meanings. In the course of the study, there were used methods of systematization, comparison, differentiation, and analysis of language data.